Large scale grid integration of renewable energy sources - Moreno-Muñoz, Antonio (IET energy engineering series, 2017)
This work presents comprehensive coverage of the means to integrate renewable power, namely wind and solar power. It looks at new approaches to meet the challenges, such as increasing interconnection capacity among geographical areas, hybridization of different distributed energy resources and building up Demand Response capabilities. This book presents an overview of the steps on the way toward 100% clean power, covering approaches like micro-storage and demand response, prosumers and energy communities and including distribution systems and microgrids -- Provided by the publisher.